Video games and well-being : press start - Kowert, Rachel, ....- (Nottingham : Palgrave Macmillan, 2019)
This book examines how video game mechanics and narratives can teach players skills associated with increased psychological well-being. It integrates research from psychology, education, ludology, media studies, and communication science to demonstrate how game play can teach skills that have long been associated with increased happiness and prolonged life satisfaction, including flexible thinking, openness to experience, self-care, a growth mindset, solution-focused thinking, mindfulness, persistence, self-discovery and resilience. The chapters in this volume are written by leading voices in the field of game studies, including researchers from academia, the video gaming industry, and mental health practitioners paving the way in the field of “geek therapy.”
Keywords: geneeskunde; psychologie; video games